Acute pain management in the neonate. Issue 1 (January 2023) - Masters, James; Arnold, Philip; Diwan, Rishi
Abstract: Neonates may require a variety of painful procedures during their time in hospital. The stark differences in physiology and drug handling in this age group pose the attending clinician a significant and unique challenge when considering appropriate analgesic strategies. A multimodal approach, with careful modification of established analgesic practices, is required in order to both minimize the negative sequelae of pain and limit adverse effects. Those tasked with the care of neonates should be familiar with the different analgesic options at their disposal, utilizing a combination of non-pharmacologic, pharmacologic and interventional strategies in order to improve patient care.